Faktor yang Mempengaruhi Kejadian Malaria: Tinjauan Pustaka - Landudjama, Leni; Noviana, Ineke; Mulu, Servasius To'o Jala; Kitu, Irene Febriany Mamo (JURNAL KESEHATAN PRIMER, 2022)
Background: Malaria is an acute febrile disease caused by the plasmodium parasite that is transmitted to humans through the bite of an infected female Anopheles mosquito. Highly endemic districts of malaria are still concentrated on Sumba Island. Objective: to identify factors influencing the incidence of malaria in East Nusa Tenggara. Method: This type of research is a literature review, literature search using the Google Scholar, ScinceDirect, PubMed, and Proquest databases with the keywords 'Factors influencing the incidence of malaria cases in East Nusa Tenggara'. Inclusion criteria are journals published in the period 2021-2022, original journal types of articles with quantitative and qualitative research methods, journals can be fully accessed via full text pdf files, articles taken are national and international journal articles. Results: Factors influencing the incidence of malaria are population mobility or history of travel to malaria endemic areas, living habits and going out of the house especially at night without using mosquito protection, low public awareness of the incidence of malaria, and the presence of mosquito breeding grounds in residential areas. The suggestions in this study are to maintain environmental cleanliness, increase awareness and lifestyle habits by implementing malaria prevention and limiting population mobility to malaria endemic areas.